Evaluasi Program PAMSIMAS: Studi Kebijakan Penyediaan Air Minum dan Sanitasi di Kecamatan Muruk Rian Kabupaten Tana Tidung - Junaeny, Fitriah; Darmanto, Darmanto; Darmi, Titi (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
This study aims to determine the evaluation of the implementation policy of community-based drinking water and sanitation provision (PAMSIMAS) in Muruk Rian District, Tana Tidung Regency. The research method used is qualitative with a descriptive approach with a research focus on policy evaluation criteria consisting of effectiveness, efficiency, adequacy, equity, responsiveness and accuracy of PAMSIMAS policy implementation. Informants in this study were the Head of Bappeda and Litbang, Village Head, PAMSIMAS Facilitator, Pokja, Disaster Management Group and PAMSIMAS beneficiary communities. Data sources in this study consist of two, namely primary and secondary data sources. Data collection techniques are observation, interviews and documentation with data analysis techniques, namely data reduction, data presentation and drawing conclusions. The results of the study indicate that overall the implementation of the PMASIMAS policy in the target villages in Muruk Rian District is running well, this can be seen from the policy evaluation indicators such as effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy of the implementation of the development and development of PAMSIMAS facilities and infrastructure can meet the needs of the target community and this policy can overcome the access gap for communities far from urban centers, especially communities who do not yet have access to PDAM water.